Methodological aspects of the study of the problems of competitive development of Rebuplic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
This article is dedicated to the disclosure of the problems of modern development of the national economy. The focus is on methodological aspects of the study of the competitive development problems of the national economic system. The theoretical and methodological and conceptual approaches to the development and implementation of economic policies of improving the stability of the national economic system in an unstable global processes were considered.
Keywords: economy; competitiveness; economic policy; social and economic efficiency; self-development.